Un problema de localización de plantas de gran escala - Gutiérrez Andrade, Miguel Ángel (2000)
We develop an heuristic algorithm and its implementation for solving a large scale facility location problem, where there can arise over 640 facilities to be located in Mexico. Originally, we tried to obtain an exact solution to the problem, using two classical techniques: Benders decomposition, and branch and bound. Both techniques  are adequate and efficient for solving low-scale problems, but computer implementations for this problem did not converge after several hours of computing. Hence, we needed a good solution even if it was not exact. We used the simulated annealing technique with excellent results.